US trends in the association of suicide ideation/behaviors with marijuana use among adolescents ages 12–17 and differences by gender and race/ethnicity - Flores, Michael William; Granados, Saul; Cook, Benjamin Lê (Frontiers in Psychiatry, 2023)
Background: In the US over the past decade, there has been a steady increase in marijuana use rates among adolescents, in part due to marijuana legalization laws. It is unknown whether these greater marijuana use rates are associated with rising rates of adolescent suicide ideation and behaviors (plan and attempt) or whether these associations differ by gender or race/ethnicity. Objective: To determine whether marijuana use is associated with suicide ideation/ behaviors among adolescents and if differences exist by gender and race/ethnicity. Methods: Using the 2015-2019 National Surveys on Drug Use and Health, we assessed the relationship between marijuana use frequency and suicide ideation/behaviors among adolescents (12-17, n=73,986). We also examined the association with marijuana use disorder (MUD) and assessed differences by gender and race/ethnicity. Marijuana use frequency in the past year was categorized as no use, non-weekly use, and weekly-plus use. We estimated multivariable logistic regression models, adjusting for sociodemographics, health status, common co-occurring behavioral health disorders, and criminal history. For interpretability, regression coefficients were converted into predicted probabilities using predictive margin methods. Results: In primary analyses, adolescents with non-weekly use and weekly-plus use had higher rates of any suicide ideation, 61.5% (+10.4 percentage-points; 95%CI:7.0%-13.8%) and 64.5% (+13.4 percentage-points; 95%CI:9.1%-17.7%), relative to no use (51.1%). Non-weekly and weekly-plus use was associated with higher rates of any suicide plan 58.2% (+11.8 percentage-points; 95%CI:7.8%-16.0%) and 59.0% (+12.6 percentage-points; 95%CI:6.4%-18.9%), and any suicide attempt, 42.0% (+11.6 percentage-points; 95%CI:7.0%-16.2%) and 47.3% (+16.9 percentage-points; 95%CI:10.9%-22.9%) compared to no use (46.4% and 30.4%, respectively). Similar results were found among adolescents with a MUD (all p<0.05). Positive associations between marijuana use and suicide ideation/behaviors persisted among males and females as well as White, Black, and Latinx adolescents (all p<0.05). Conclusions: Between 2015-2019, suicide ideation/behaviors increased for adolescents that used marijuana. As marijuana is legalized in more states, public health efforts are needed to curb increases in marijuana use among adolescents and to better understand the causal linkages between marijuana use and suicide ideation/behaviors.